TONNESSEN, Elise Seip; FORSGREN, Frida. (Ed.) Multimodality and Aesthetics. New York: Routledge, 2019. 360 p. ISBN-10: 1138103519. ISBN-13: 978-1138103511. - Galvão, Rosane Queiroz (Cadernos de Linguagem e Sociedade, 2021)
Resenha do livro TONNESSEN, Elise Seip; FORSGREN, Frida. (Ed.) Multimodality and Aesthetics. New York: Routledge, 2019. 360 p. ISBN-10: 1138103519. ISBN-13: 978-1138103511.